An Investigation of Teaching Strategy in the Distance Learning Mathematics Classroom - Tiffany DePriter (Journal of Educators Online, 2013)
Distance learning has become increasingly popular among higher learning institutions, and more academic disciplines, such as mathematics, are now being offered at a distance. This experimental study investigated whether an objectivist-based teaching strategy or a constructivist-based teaching strategy yields greater achievement scores for adult students learning mathematics at a distance. A pretest-posttest control-group design was used, with a sample of 35 students. Two researcher-made test instruments, consisting of multiple-choice and brief constructed response/extended constructed response (BRC/ECR) items, were used to measure students’ understanding of mathematics topics both before and after the teaching intervention. While the results of t-tests and ANCOVA showed no statistically significant difference in achievement scores between the groups, the findings indicate that both teaching strategies are viable in the distance learning mathematics classroom